Value Creation and Value Appropriation. (November 2022) - Kumar, V.; Srivastava, Rajendra
This article discusses the nine research studies compiled for the Journal of Creating Value (JCV) special issue, which has embarked on securing a deeper understanding of the divergent aspects of defining, measuring and maximizing value. Altogether, the nine studies collectively offer insights in this regard that are applicable to a wide range of organizations. This special issue runs the gamut of management actions in terms of value management and prepares companies for the future. The proposed classification framework in this article categorizes the nine studies based on their focus on value creation potential and value appropriation potential. Further, this article identifies and delineates future research directions that extend beyond the path forward identified by each of the studies themselves. Overall, this article is aimed to serve as a guide to understand and appreciate this special issue on a topic of vital interest.